Emulgel: A Topical Preparation - Parihar, Nikhita; Saini, Mahendra; Soni, Shankar Lal; Sharma, Vandana (Asian Journal of Pharmaceutical Research and Development, 2020)
Emulgel is an emerging topical drug formulation which is becoming increasingly popular due to its advantages over the conventional topical preparations. The emulgel is a combination of an emulsion and a gel and thus has a dual release control system. Its biggest and most favorable advantage has been the ability to incorporate hydrophobic drugs, thus making it emerge as a more popular choice these days. The emulgel is also greaseless, transparent; it can be easily spread and removed, has a long shelf- life, is thixotropic and is also pleasant looking. The emulgel is turning out be a preferred choice for cosmetic and dermatological preparations and its use and application will accelerate in the coming future.